Appendectomy and Risk of Subsequent Diverticular Disease Requiring Hospitalization: A Population-Based Case-Control Study. Issue 7 (July 2018) - Sköldberg, Filip; Olén, Ola; Ekbom, Anders; Schmidt, Peter T.
Abstract : BACKGROUND: Appendicitis and acute diverticulitis share clinical features and are both influenced by genetic and environmental factors. Appendectomy has been positively associated with diverticular disease in hospital-based case–control studies. OBJECTIVE: The aim of the present study was to investigate, in a population-based setting, whether appendectomy, with or without appendicitis, is associated with an altered risk of hospitalization with diverticular disease. DESIGN: This was a population-based case-control study. SETTINGS: The study was based on national healthcare and population registers. PATIENTS: We studied 41, 988 individuals hospitalized between 2000 and 2010 with a first-time diagnosis of colonic diverticular disease and 413, 115 matched control subjects. MAIN OUTCOME MEASURES: The association between appendectomy with or without appendicitis and diverticular disease was investigated by conditional logistic regression, including a model adjusting for hospital use. RESULTS: A total of 2813 cases (6.7%) and 19, 037 controls (4.6%) had a previous record of appendectomy (appendectomy with acute appendicitis: adjusted OR = 1.31 (95% CI, 1.24–1.39); without appendicitis: adjusted OR = 1.30 (95% CI, 1.23–1.38)). Appendectomy was most strongly associated with an increased risk of diverticular disease within 1 year (with appendicitis: adjusted OR = 2.26 (95% CI, 1.61–3.16); without appendicitis: adjusted OR = 3.98 (95% CI, 2.71–5.83)), but the association was still present ≥20 years after appendectomy (with appendicitis: adjusted OR = 1.22 (95% CI, 1.12–1.32); without appendicitis: adjusted OR = 1.19 (95% CI, 1.10–1.28)). LIMITATIONS: Detailed clinical information on the cases was not available. There were unmeasured potential confounders, such as smoking and dietary factors. CONCLUSIONS: The findings are consistent with a hypothesis of appendectomy causing an increased risk of diverticular disease, for example, by affecting the mucosal immune system or the gut microbiome. However, several other mechanisms may contribute to, or account for, the positive association, including a propensity for abdominal pain increasing the risk of both the exposure and the outcome. SeeVideo Abstract athttp://links.lww.com/DCR/A604 . Abstract : Supplemental Digital Content is available in the text.